2018
DOI: 10.4064/cm7242-6-2017
|View full text |Cite
|
Sign up to set email alerts
|

Sets of lengths in atomic unit-cancellative finitely presented monoids

Abstract: For an element a of a monoid H, its set of lengths L(a) ⊂ N is the set of all positive integers k for which there is a factorization a = u 1 ·. . .·u k into k atoms. We study the system L(H) = {L(a) | a ∈ H} with a focus on the unions U k (H) ⊂ N which are the unions of all sets of lengths containing a given k ∈ N. The Structure Theorem for Unions -stating that for all sufficiently large k, the sets U k (H) are almost arithmetical progressions with the same difference and global bound -has found much attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…We infer from (13) and point (i) that ρ k+m,i − ρ k,i = ρ k+m − ρ k and λ k+m,i − λ k,i = λ k+m − λ k for all large k, which, by (12), is enough to conclude. Theorem 2.15.…”
Section: Subadditive Familiesmentioning
confidence: 78%
See 1 more Smart Citation
“…We infer from (13) and point (i) that ρ k+m,i − ρ k,i = ρ k+m − ρ k and λ k+m,i − λ k,i = λ k+m − λ k for all large k, which, by (12), is enough to conclude. Theorem 2.15.…”
Section: Subadditive Familiesmentioning
confidence: 78%
“…The Structure Theorem for Unions holds for a wealth of cancellative monoids [8,9], and recent work has revealed that the theorem admits a "purely additive" counterpart: This was made possible by the introduction of directed families, and has led, for the first time, to the extension of the theorem to a non-cancellative setting, see [4,Theorem 2.2 and § 3] and [13,Theorem 3.6].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the definition of the set of lengths of elements in monoid in [4], the definition of length of d D ∈ can be given certainly since Lemma 2.2.…”
Section: Preliminariesmentioning
confidence: 99%
“…L(H) is additively closed in certain Krull monoids stemming from module theory ([1, Section 6.C]). Examples in a non-cancellative setting can be found in [20,Theorem 4.5] and a more detailed discussion of the property of being additively closed is given in [18].…”
Section: Sincementioning
confidence: 99%